2016
DOI: 10.1371/journal.pone.0146541
|View full text |Cite|
|
Sign up to set email alerts
|

Empirical Study of User Preferences Based on Rating Data of Movies

Abstract: User preference plays a prominent role in many fields, including electronic commerce, social opinion, and Internet search engines. Particularly in recommender systems, it directly influences the accuracy of the recommendation. Though many methods have been presented, most of these have only focused on how to improve the recommendation results. In this paper, we introduce an empirical study of user preferences based on a set of rating data about movies. We develop a simple statistical method to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 52 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Ghauth and Abdullah [39] proposed a framework that recommends learning materials based on content similarity and user ratings. In predicting user preferences, Zhao and Shen [40] conducted an empirical study of movie ratings and proposed a preference model that eliminates impracticable predictions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ghauth and Abdullah [39] proposed a framework that recommends learning materials based on content similarity and user ratings. In predicting user preferences, Zhao and Shen [40] conducted an empirical study of movie ratings and proposed a preference model that eliminates impracticable predictions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that this preference information could be used for advertising, product recommendation, and various other personalized social media services. A simple statistical method was developed by Zhao and Shen (2016) to investigate the characteristics of user preferences on the MovieLens website. Their results show that users in small cliques always share similar opinions on movies to other clique members.…”
Section: Online User Surveys Via Social Mediamentioning
confidence: 99%